MANAJEMEN LINGKUNGAN PENDIDIKAN (STUDI TENTANG PENGELOLAAN SAMPAH SEBAGAI UPAYA PEMBENTUKAN SIKAP PEDULI LINGKUNGAN) DI MTs NEGERI 2 BANDAR LAMPUNG - Eva Lestari; Yetri Hasan; Yosep Aspat Alamsyah; Riyuzen Praja Tuala (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze educational environmental management through waste management as an effort to form an environmental awareness attitude in students at MTs Negeri 2 Bandar Lampung. The research method uses a descriptive qualitative approach, involving the principal, teachers, and students. Data collection was carried out through semi-structured interviews, non-participant observation, and documentation, while data analysis used the interactive model of Miles and Huberman through the stages of data reduction, data presentation, and drawing conclusions with triangulation of sources and techniques to ensure data validity. The results of the study indicate that waste management in madrasas has been implemented through management stages including planning, organizing, implementing, and controlling the program. The novelty of this study lies in waste management which is understood as part of educational environmental management that plays a role in fostering environmental awareness and attitudes in students.